Gangs: an introduction - Sanders, Bill (Oxford University Press, 2017)
Machine generated contents note: -- Preface -- Acknowledgments -- About the Author -- Introduction -- A History of Respectable Fears -- Estimating the Number of Gangs, Gang Members, and Gang Crimes -- Chapter 1. Early Research and Perspectives -- 18th- and 19th-Century Gangs -- Thrasher: The First Gang Researcher -- Gangs as Delinquent Subcultures -- Differential Opportunity Theory -- Lower-Class Culture and Adolescence -- Gangs as Near-Group -- Group Process and Gang Delinquency -- Roles within Gangs: Keiser and the Vice Lords -- Street Gangs and Street Workers -- Chapter 2. Definitions, Daily Life, Dynamics, and Risk Factors -- Sociological Definitions -- Legal Definitions -- What Gangs Are Not -- A Structured Typology -- Daily Life -- Positive and Negative Aspects -- Interrelated Dynamics -- Membership -- Organization -- Subgroups -- Intensity -- The Causes and Correlates Studies -- Protective Factors -- Chapter 3. Race, Migration, and Immigration -- A Brief Note on Race Relations in American History -- Black Gangs -- The Crips and Bloods -- Latino Gangs -- The People Nation and the Folks Nation -- A Typology of Mexican American Gangs -- Asian and Asian Pacific Islander Gangs -- Chinese Gangs -- Southeast Asian Gangs -- Filipino Gangs -- Native American Gangs -- White Gangs -- Skinheads -- Skinheads as Gangs -- Nazi Low Riders -- Chapter 4. Females -- Early Studies and Stereotypes -- Increases in Female Arrests and Incarceration -- Further Developments in Female Gang Research -- Differences and Similarities between Gang Females and Males -- The Number of Female Gangs and Gang Members -- Different Types of Female Gangs -- Female Gang Violence -- Sexual Victimization -- Identity, Femininity, Sexuality, and Respect -- Pregnancy and Motherhood -- Prosocial Functions and Post-Gang Lives -- Chapter 5. Drug Use and Sales -- Substance Use Patterns -- Alcohol -- Marijuana -- Other Illicit Drugs -- Attitudes about Hard Drug Use -- Drug Addiction -- Drug Selling -- Myths ab --- "Gangs: An Introduction provides a wide-ranging overview ideal for courses on gangs. Opening with a discussion of early research and perspectives from the late 1920s until the early 1970s, the book then moves on to cover sociological and legal definitions of gangs; daily life and risk and protective factors; race and immigration; female gang members; drug use and selling; violence and victimization; the cultural criminology of gangs; theories on gangs and gang behaviors; desistance; suppression, intervention, and prevention; and more. FEATURES * A focus on theories of gangs, rather than on criminological theories * Original contributions to the gang literature * An emphasis on evidence-based practices * Examples of real-life court cases * Interview excerpts from gang members, drawn from the author's research *Media Check! sections in each chapter featuring examples from movies, documentaries, TV shows, and music"--- "This is a textbook for undergraduate majors and non-majors in an introductory Juvenile Delinquency course or course on Gangs"--